PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA ANIMASI DAN SIMULASI TERHADAP HASIL BELAJAR IPA SISWA - Bara, Ferdiyanto Marnolius; Harso, Aloisius; Astro, Richardo Barry (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to determine the effect of the discovery learning model assisted by animation media on the learning outcomes of class eight students of St Gabriel Ndona Catholic Middle School for the 2022/2023 academic year. This type of research is a pre-experimental design (One Shoot Case Study) with a quantitative approach. Data collection techniques are in the form of objective tests. The population in this study were students of class eight, St. Gabriel Ndona's Catholic First Middle School. The study sample consisted of 32 students obtained from the saturated sampling technique. According to the analysis using the SPSS-V24 application, the results showed that the discovery learning model affected the science learning outcomes of class eight students of SMPK St Gabriel Ndona. This is shown by the results of data analysis for science learning outcomes with sig. 0.05, the confidence level is 95%, and the value of t count = 5.838, so the sig value is obtained. 0.00 < 0.05 so that H0 is rejected and H1 is accepted. The profile of students' thinking abilities in the cognitive domain shows good results, where 80% of students have good thinking skills that influence student learning outcomes. The study had various obstacles, including the lack of learning facilities such as computers, so learning was done in groups.